Форма линии магнитного резонанса в порошках La0,7Ba0,3MnO3 при низких температурах - Яковенко, В.М.; Белозоров, Д.П.; Тарапов, С.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The experimental study of ferromagnetic resonance (FMR) in La0.7Ba0.3MnO3 powder having the nanosize particles (~50 μm) at very low temperatures (0.35 K ≤ T ≤ 4.2 K) has been performed. The essential frustration of the FMR lineshape is revealed. The FMR-model developed by the authors earlier is the background of the lineshape simulation. It is shown that the lineshape can be described completely by varying not more than one macroscopic parameter which is responsible for the anisotropy of the spin-system caused by the applied magnetic field.